Biochemical marker discovery, testing and evaluation for facilitating OA drug discovery and development. Issue 2 (February 2018) - Bay-Jensen, Anne-Christine; Thudium, Christian S.; Gualillo, Oreste; Mobasheri, Ali
Graphical abstract: Highlights: Osteoarthritis (OA) is the most common form of joint disease but there are no drugs for its effective treatment. For many years OA was considered a homogeneous disease but there are several different OA phenotypes, which complicates traditional approaches for developing novel therapeutics. New biomarkers can be used for objective patient phenotyping and to facilitate OA drug discovery and development by the pharmaceutical industry. Abstract : Osteoarthritis (OA) is the most common form of joint disease. This presents the OA research community and pharmaceutical companies developing disease-modifying OA drugs (DMOADs) with great opportunities. The different OA subtypes complicate the traditional approaches for developing new treatments. If we can identify new markers that can distinguish different subtypes this could greatly facilitate drug development from early discovery to late clinical development. Nevertheless, the current approaches result in poorly targeted treatments and the inability to recruit the right patients for clinical trials. Thus, there is an urgent medical need for objective biomarker tools for patient phenotyping.